2012
DOI: 10.1371/journal.pone.0036507
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Burkholderia pseudomallei in Recurrent Melioidosis

Abstract: Burkholderia pseudomallei, the etiologic agent of human melioidosis, is capable of causing severe acute infection with overwhelming septicemia leading to death. A high rate of recurrent disease occurs in adult patients, most often due to recrudescence of the initial infecting strain. Pathogen persistence and evolution during such relapsing infections are not well understood. Bacterial cells present in the primary inoculum and in late infections may differ greatly, as has been observed in chronic disease, or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
114
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 67 publications
4
114
0
Order By: Relevance
“…VgrG5 is conserved and functionally interchangeable between Burkholderia pseudomallei and near-neighbor species. Sequence comparisons with VgrG5 encoded by the B. pseudomallei reference genome from strain 1026b (40), the parent of Bp340 (36), indicates high levels of conservation with orthologs in other Pseudomallei group Burkholderia species and strains ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…VgrG5 is conserved and functionally interchangeable between Burkholderia pseudomallei and near-neighbor species. Sequence comparisons with VgrG5 encoded by the B. pseudomallei reference genome from strain 1026b (40), the parent of Bp340 (36), indicates high levels of conservation with orthologs in other Pseudomallei group Burkholderia species and strains ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…B. pseudomallei strain 1026b (Bp1026b) is a clinical isolate from a patient with septicemic melioidosis in Thailand (45,46). Culture stocks were grown overnight in Luria-Bertani broth (LB) (BD Biosciences, San Jose, CA) at 37°C with shaking.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we genetically characterized the T2SS of B. pseudomallei 1026b and found that two distinct gsp loci were required for the export of protease, phospholipase C (PLC), and lipase activities (21). The 1026b genome was recently completed (22), and the gspD to -N and gspO loci correspond to BP1026B_I0008 to BP1026B_I0016, BP1026B_I0018, BP1026B_I0019, and BP1026B_I0298, respectively. The specific proteins secreted by T2SS in B.…”
mentioning
confidence: 99%